African domestic poultry genetic resources, diversity, and unique features - Dessie, Tadelle; Tiambo, Christian K.; Banda, L.J.; Lawal, R.A.; Ommeh, S.C.; Gondwe, T.; Esatu, Wondmeneh; Adeleke, M.A.; Hanotte, Olivier H. (Springer, 2025)
This chapter provides a detailed account of African domestic poultry genetic resources, their diversity, and unique features. It aims to bring together information to provide a comprehensive picture of the topic. Section 7.1 introduces African poultry genetic resources, their importance, and previous interventions conducted to better utilize this important resource. Section 7.2 deals with the origin of poultry genetic resources and their dispersal into Africa. The introduction of domesticated chickens into Africa is not well documented. Although indigenous birds have several adaptive traits and associated genes that are important in the tropics, the real value of indigenous chicken breeds is often underestimated. They have a poor appearance, relatively low productivity, and are consequently considered to have low value compared to their improved commercial counterparts. Chicken genetic resources are endangered and under-conserved. However, there has been recent emphasis on local chicken breed development and conservation, which has gained attention. The section demonstrates how chickens have become a key part of the African poultry production system and how they can remain vital and instrumental, considering the current climate change. Sections 7.3, 7.4, 7.5 and 7.6 describe the available chicken and duck resources in different parts of Africa and outline their unique features and population estimates. Considering the population size of these genetic resources, conservation efforts to support their utilization are addressed in Sect. 7.8. Furthermore, the importance of conserving poultry genetic resources using germplasm cryobanking (cryoconservation) is described. Section 7.10 describes genetic improvement attempts in Africa involving indigenous chicken populations. The information appears to be limited to a few examples, as not many improvement programs are ongoing, and information on some programs is not available. Section 7.11 describes the major constraints of poultry production in Africa, followed by the economic contributions in Sect. 7.12. The last chapter implies the way forward in the utilization of poultry genetic resources in Africa.